2019
DOI: 10.17240/aibuefd.2019.19.49440-519075
|View full text |Cite
|
Sign up to set email alerts
|

Zi̇hi̇n Engelli̇ Öğrenci̇lere Çikarma İşlemi̇ Öğreti̇mi̇nde Sabi̇t Bekleme Süreli̇ Öğreti̇mle Sunulan Nokta Beli̇rleme Tekni̇ği̇ni̇n Etki̇li̇li̇ği̇

Abstract: ÖZBu araştırmanın amacı, sabit bekleme süreli öğretim yöntemiyle sunulan nokta belirleme tekniğinin zihin yetersizliği olan bireylere çıkarma işlemi öğretiminde etkililiğini, kalıcılığını ve genellemesini belirlemektir. Araştırmada zihin yetersizliği olan üç öğrenci yer almıştır. Tek denekli araştırma desenlerinden denekler arası yoklama evreli çoklu yoklama modeli kullanılmıştır. Araştırmanın bağımsız değişkeni sabit bekleme süreli öğretim yaklaşımına dayalı olarak sunulan nokta belirleme tekniği, bağımlı değ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Having acquired the target skill, the participating students were able to generalise problemsolving skill to a different environment and tool. This finding of the current study corresponds to other studies in the literature (Badır-Polat & Yıkmış, 2019;Calik & Kargin, 2010;Eliçin et al, 2013;Scott, 1993;Simon & Hanrahan, 2004). In those studies, it was found that the participants with intellectual disability were able to generalise the targeted various mathematical concepts and skills acquired through the TouchMath technique to different situations.…”
Section: Discussionsupporting
confidence: 91%
“…Having acquired the target skill, the participating students were able to generalise problemsolving skill to a different environment and tool. This finding of the current study corresponds to other studies in the literature (Badır-Polat & Yıkmış, 2019;Calik & Kargin, 2010;Eliçin et al, 2013;Scott, 1993;Simon & Hanrahan, 2004). In those studies, it was found that the participants with intellectual disability were able to generalise the targeted various mathematical concepts and skills acquired through the TouchMath technique to different situations.…”
Section: Discussionsupporting
confidence: 91%